Hide and Seek: The Interplay Between Zika Virus and the Host Immune Response - Lee, Lim Jack; Komarasamy, Thamil Vaani; Adnan, Nur Amelia Azreen; James, William; RMT Balasubramaniam, Vinod (Frontiers in Immunology, 2021)
Zika virus received worldwide attention over the past decade when outbreaks of the disease were found to be associated with severe neurological syndromes and congenital abnormalities. Unlike most other flaviviruses, ZIKV can spread through sexual and transplacental transmission, adding to the complexity of Zika pathogenesis and clinical outcomes. In addition, the spread of ZIKV in flavivirus-endemic regions, and the high degree of structural and sequence homology between Zika and its close cousin Dengue have raised questions on the interplay between ZIKV and the pre-existing immunity to other flaviviruses and the potential immunopathogenesis. The Zika epidemic peaked in 2016 and has affected over 80 countries worldwide. The re-emergence of large-scale outbreaks in the future is certainly a possibility. To date, there has been no approved antiviral or vaccine against the ZIKV. Therefore, continuing Zika research and developing an effective antiviral and vaccine is essential to prepare the world for a future Zika epidemic. For this purpose, an in-depth understanding of ZIKV interaction with many different pathways in the human host and how it exploits the host immune response is required. For successful infection, the virus has developed elaborate mechanisms to escape the host response, including blocking host interferon response and shutdown of certain host cell translation. This review provides a summary on the key host factors that facilitate ZIKV entry and replication and the mechanisms by which ZIKV antagonizes antiviral innate immune response and involvement of adaptive immune response leading to immunopathology. .